2004
DOI: 10.1016/j.orthres.2003.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Intramembranous ossification mechanism for bone bridge formation at the growth plate cartilage injury site

Abstract: Salter's type I11 and type IV growth plate injuries often induce bone bridge formation at the injury site. To understand the cellular mechanisms, this study characterized proximal tibia1 transphyseal injury in rats. Histologically, bony bridge trabeculae appeared on day 7, increased on day 10, and became well-constructed on day 14 with marrow. Prior to and during bone bridging, there was no cartilage proteoglycan metachromatic staining and no collagen-)< immunostaining at the injury site, nor was there any up-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
133
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(146 citation statements)
references
References 21 publications
13
133
0
Order By: Relevance
“…Vimentin, one of intermediate filament proteins, is known to be a marker of osteoprogenitor cells (Watanabe et al, 1993;Shapiro et al, 1995;Xian et al, 2004) and is expressed in the cell body and processes of osteoblasts and osteocytes (Shapiro et al, 1995). Our recent study (Abe et al, 2012) demonstrated ligament-specific distributions of vimentin-positive mesenchyme in the developing atlanto-occipital junction.…”
Section: Methodsmentioning
confidence: 65%
“…Vimentin, one of intermediate filament proteins, is known to be a marker of osteoprogenitor cells (Watanabe et al, 1993;Shapiro et al, 1995;Xian et al, 2004) and is expressed in the cell body and processes of osteoblasts and osteocytes (Shapiro et al, 1995). Our recent study (Abe et al, 2012) demonstrated ligament-specific distributions of vimentin-positive mesenchyme in the developing atlanto-occipital junction.…”
Section: Methodsmentioning
confidence: 65%
“…Initially, neutrophils arrive to the fracture site as detected in a rat model of fracture [24]. Neutrophils have an anti-septic effect and clear the damaged cells and debris [25,26].…”
Section: Clearing Of Damaged Areasmentioning
confidence: 99%
“…In a rat model of tibia fracture, neutrophils were detected at the fracture callus on day 1 and remained for few days after the fracture (28). In association with high-level of chemokine, cytokine-induced neutrophil chemoattractant-1 (CINC-1), neutrophils migrate across the endothelium into hematoma site (29).…”
Section: Neutrophilsmentioning
confidence: 99%